2017
DOI: 10.1111/bjc.12147
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in preferences for psychological treatment, coping strategies, and triggers to help‐seeking

Abstract: Objective. There is some evidence that men and women deal with stress in different ways; for example, a meta-analysis found that women prefer to focus on emotions as a coping strategy more than men do. However, sex differences in preferences for therapy is a subject little explored. Design.A cross-sectional online survey.Method. Participants (115 men and 232 women) were recruited via relevant websites and social media. The survey described therapies and asked participants how much they liked each. Their coping… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
162
5
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 247 publications
(189 citation statements)
references
References 25 publications
18
162
5
4
Order By: Relevance
“…This is in line with recent literature (Ip et al, 2016;Liddon et al, 2017) and emphasises the importance of researching and accommodating sex preferences of prospective clients. This is in line with recent literature (Ip et al, 2016;Liddon et al, 2017) and emphasises the importance of researching and accommodating sex preferences of prospective clients.…”
Section: Effect Of Sex But Not Of Problem Type On Preference For Thsupporting
confidence: 89%
See 1 more Smart Citation
“…This is in line with recent literature (Ip et al, 2016;Liddon et al, 2017) and emphasises the importance of researching and accommodating sex preferences of prospective clients. This is in line with recent literature (Ip et al, 2016;Liddon et al, 2017) and emphasises the importance of researching and accommodating sex preferences of prospective clients.…”
Section: Effect Of Sex But Not Of Problem Type On Preference For Thsupporting
confidence: 89%
“…Earlier studies found unilateral preferences for male therapists (Bernstein, Hofmann, & Wade, 1987), whereas more recent research observed unilateral preferences for female therapists (Landes, Burton, King, & Sullivan, 2013) or no preference (Ip et al, 2016;Liddon, Kingerlee, & Barry, 2017). Earlier studies found unilateral preferences for male therapists (Bernstein, Hofmann, & Wade, 1987), whereas more recent research observed unilateral preferences for female therapists (Landes, Burton, King, & Sullivan, 2013) or no preference (Ip et al, 2016;Liddon, Kingerlee, & Barry, 2017).…”
Section: Preferences For Therapists' Sexmentioning
confidence: 94%
“…Although the difference in help‐seeking behaviour between men and women among NOK is surely notable, it does confirm previous studies showing that women to a much higher degree seek various professional psychosocial support and counselling and that female partners to cancer patients report higher levels of anxiety and psychological distress than male partners . Common explanations for gendered help‐seeking behaviour have been that men are more likely to find support in their family and social network and are more reluctant to engage in interventions focusing on emotional disclosure . A plausible suggestion for gendered differences might also be that not only people's help‐seeking behaviour but also health personnel's referrals are influenced by norms and ideas of men as stoic and women as help‐seeking, ie, that women are more inclined and more often encouraged to engage in psychosocial support while distressed and that men might seek other types of support.…”
Section: Discussionsupporting
confidence: 66%
“…Case managers and carers should be provided psychoeducation to inform them about sex differences in behaviours and mental health. Apart from the differences described here, there can also be other considerations including sex differences in health and mental health literacy (Cotton, Wright, Harris, Jorm, & Mcgorry, ), help‐seeking (Liddon, Kingerlee, & Barry, ), coping and resilience (Liddon et al, ), and willingness to accept support (Liddon et al, ). Upskilling case managers and carers in these issues is especially important given that young people do not necessarily instigate help‐seeking for mental health and behavioural problems (Rickwood, Deane, & Wilson, ).…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the differences described here, there can also be other considerations including sex differences in health and mental health literacy (Cotton, Wright, Harris, Jorm, & Mcgorry, 2006), help-seeking (Liddon, Kingerlee, & Barry, 2018), coping and resilience (Liddon et al, 2018), and willingness to accept support (Liddon et al, 2018).…”
Section: Implications For Clinical Practice Future Research and Pmentioning
confidence: 96%